Comparative Analysis of Fault Tolerance Techniques in Cloud Computing: A Case of Armangerayan Co. - Rasol Roveicy, Mohammadreza; Massoud Bidgoli, Amir (International Journal of Engineering and Technology, 2026)
Cloud computing is the outcome of in demand service evolution in computing paradigm of large scale distributed computing. It is known as an adaptable technology as it furnishes integration of software and resources which are highly scalable, and most often are prone to failure. Fault Tolerance is concerned with all the techniques to enable system to tolerate software as well as hardware faults remaining in a system after its development. Recent studies have undertaken by various researchers depict the performance of some techniques such as HA proxy, SHelp, Azure, Hadoop etc. There is no evidence to show the overall performance of Elastic Load Balancing as compared with other architectures. The purpose of this paper is to study the fault tolerance techniques in cloud environment by using two different techniques namely HA proxy and Amazon ELB in order to improve availability and reliability when one server goes down for any reasons such as DOS attacks in the case of Armangerayan Co. Performance of two techniques have been compared while considering important factors as connecting time, processing time, waiting time and fail requests. Results reveal that the Amazon ELB in practice has been performing better than HA-proxy in our case study.